First observations of $\bar{B}_s^0→ D^+D^-$, $D_s^+D^-$ and $D^0\bar{D}^0$ decays - collaboration, L; Aaij, R; Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2013)
First observations and measurements of the branching fractions of the $\bar{B}_s^0→ D^+D^-$, $\bar{B}_s^0→ D_s^+D^-$ and $\bar{B}_s^0→ D^0\bar{D}^0$ decays are presented using 1.0 fb$^{-1}$ of data collected by the LHCb experiment. These branching fractions are normalized to those of $\bar{B}^0→ D^+D^-$, $B^0→ D_s^+D^-$ and $B^-→ D^0D_s^-$, respectively. An excess of events consistent with the decay $\bar{B}^0→ D^0\bar{D}^0$ is also seen, and its branching fraction is measured relative to that of $B^-→ D^0D_s^-$. Improved measurements of the branching fractions ${\cal{B}}(\bar{B}_s^0→ D_s^+D_s^-)$ and ${\cal{B}}(B^-→ D^0D_s^-)$ are reported, each relative to ${\cal{B}}(B^0→ D_s^+D^-)$. The ratios of branching fractions are {-0.2in} {center} {align*} {{\cal{B}}(\bar{B}_s^0→ D^+D^-)\over {\cal{B}}(\bar{B}^0→ D^+D^-)} and= 1.08± 0.20±0.10, {{\cal{B}}(\bar{B}_s^0→ D_s^+D^-)\over {\cal{B}}(B^0→ D_s^+D^-)} and= 0.050± 0.008±0.004, {{\cal{B}}(\bar{B}_s^0→ D^0\bar{D}^0)\over {\cal{B}}(B^-→ D^0D_s^-)} and= 0.019± 0.003±0.003, {{\cal{B}}(\bar{B}^0→ D^0\bar{D}^0)\over {\cal{B}}(B^-→ D^0D_s^-)} and= 0.0014± 0.0006±0.0002,{{\cal{B}}(\bar{B}_s^0→ D_s^+D_s^-)\over {\cal{B}}(B^0→ D_s^+D^-)} and= 0.56± 0.03±0.04, {{\cal{B}}(B^-→ D^0D_s^-)\over {\cal{B}}(B^0→ D_s^+D^-)} and= 1.22± 0.02±0.07, {align*} {center} \noindent where the uncertainties are statistical and systematic, respectively.